Application of the Fuzzy Sugeno Method in a Decision Support System for Teacher Performance Assessment - Muhammad Rezeki; Nursaka Putra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The teacher is a professional educator who has essential duties, functions, and roles in the nation's intellectual life. In order for the functions and duties attached to the functional positions of teachers to be carried out following applicable regulations, it is necessary to assess teacher performance which ensures a quality learning process at all levels of education. Currently, teacher performance evaluation uses a manual assessment system, which causes the evaluation process to be relatively long. For this reason, a decision support system is needed that can take into account all the criteria that support decision making in order to assist, speed up and simplify the decision-making process. In determining teacher performance assessment, the method used is Fuzzy Takagi-Sugeno Kang (Fuzzy Sugeno). This method was chosen because the Fuzzy Sugeno method is a decision support model where the main input uses the basic concept of finding the weighted summation. The Fuzzy Sugeno method for assessing teacher performance uses three stages: the Fuzzification Stage, the Implication Function Stage, and the Defuzzification Stage. The level of validity with Sugeno's Fuzzy Inference Systems (FIS) method for assessing teacher performance is very good.